A "Crisis of Masculinity"?: The West's Cultural Wars in the Emerging Muslim Manosphere. (14th December 2022) - Ghumkhor, Sahar; Mir, Hizer
Abstract : This article aims to frame the emergence of a new category of thought, referred to here as "Alt-Wallah", within the Islamicate which exists at the intersection between a supposed crisis of masculinity, the Alt Right, and Muslim men. This framing begins by looking at the various crises that abound both in Islam and in masculinity. We then introduce what Farris calls "femonationalism", and give some reflections on the relationship between our new category of thought and this femonationalism. This new category of thought is given the name "Alt-Wallah", and then linked to certain already existing categories of thought within the Islamicate. Other names are considered throughout the piece, as well as reasons as to why these are not adequate to describe the phenomenon in question. This is followed by an analysis of examples such as online Muslim figures Daniel Haqiqatjou, Nabeel Aziz, and others, as well as an exploration of further similarities to what is called the "fundamentalist declinist" category of thought. We then conclude with a reflection on the buffered Muslim man, and on what role the idea of the mujtahid plays in this conceptualisation of Muslim man.